Perancangan Penyiraman Tanaman dalam Pot Menggunakan Sensor Kelembaban Tanah dan Mikrokontroler Arduino Uno - Rini Puji Astutik; Tomi Ambar Prayitno (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
With the development of an era that increasingly prioritizes technology, the curiosity of a human mind expects technology that can help human work, so it is undeniable that human work can be replaced by technology. This thesis proposal will design a device that can automatically water plants in pots. In plant maintenance, not many people can care for the garden healthily and properly, especially when watering the plants. By making this automatic plant design, it will provide assistance and convenience for ornamental plant lovers. This device aims to facilitate human work that was originally done manually, to be done automatically. By using Arduino Uno as its microcontroller, Soil Moisture Sensor to assess the level of moisture in the soil, as well as motors and Infra Red Sensors to determine the location of the pot that needs water